Socio-Economic Assessment of Broadband Development in Egypt - World Bank (Washington, DC, 2013)
The Government of Egypt has recognized broadband as being of strategic importance to the country´s economic and social development and it is developing a new strategy to develop access and use of broadband networks and services. As a specific target of this strategy, the government seeks to increase broadband penetration to 20 connections per 100 inhabitants by 2013. This report is the result of the second part of the existing reimbursable technical assistance on communications by which the World Bank has been providing assistance to the government of Egypt in the development of this broadband strategy. The objective of this particular assignment is to support the policy making process to develop broadband services and infrastructure throughout Egypt and achieve substantial economic impact in the economy including specific intermediary sectors. This assignment builds of the outcomes of the previously delivered study (strategic options for broadband development, 2010) and it uses both qualitative and quantitative approaches to provide specific advisory outputs.